Chemo- and stereoselective reduction of β-keto esters by spores and various morphological forms of Mucor rouxii - Mangone, Constanza P (2002)
We report the efficient enantioselective reduction of a number of β-ketoesters by mycelial and yeast-like forms of the dimorphic fungus Mucor rouxii in a whole-cell process. Mycelial cells, grown in aerobiosis, were efficient in water, whereas the yeast-like cells, grown in anaerobic medium, were both efficient in water and in organic solvents. Almost 100% of conversion with 97% of enantiomeric excess of the (S) forms of the reduced β-ketoesters was obtained at 15 g biomass (wet weight)/mmol substrate in two hours. The fungal spores, which are the physiologically resistant form of the fungus, also catalyzed the reductive process efficiently and stereoselectively. The freeze-dried as well as the warm-air dried yeast-like cells, rehydrated in a small volume of water, maintained the same efficiency and selectivity of the reaction in organic solvents as the fresh biomass up to at least 4 months.